Feasibility study of a home treatment system for water reuse - Ferraz, Marshell; Silva, Evaristo Marcos (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The recycling or reuse of water is the process by which water, treated or not, is reused within the same cycle of its use,may be for the same purpose as was used prior to their capture or for another purpose, for the goalof reduce the consumption of drinking water from water utility. This work aims to study the feasibility of implementing a compact water treatmentsystem from rains and shared homely activities such as bathing and washing clothes. The analysis of the study includes calculations of consumption of drinking water per household, spending on equipment and system implementation, saving providedand the payback period of the investment. The proposedperformedsatisfactoryin the treatment ofwater storedwiththe use ofa coagulant(aluminumsulfate10 mg/L)and disinfectant(chlorine).Based on the indicators studied, it was concluded that for homes where the water consumption is lower than 25 m3/month, the proposed system becomes uneconomical, because the financial returns would be too logos, while for values above this, payback already it becomes attractive, around 12 months shorter.